Symptom burden as a driver of decisional regret in long‐term oropharyngeal carcinoma survivors. Issue 11 (24th July 2017) - Goepfert, Ryan P.; Fuller, C. David; Gunn, G. Brandon; Hanna, Ehab Y.; Lewin, Jan S.; Zaveri, Jhankruti S.; Hubbard, Rachel M.; Barrow, Martha P.; Hutcheson, Katherine A.
Abstract: Background: The purpose of this study was to characterize decisional regret and its association with symptom burden in a large cohort of oropharyngeal carcinoma (OPC) survivors. Methods: A cross‐sectional survey was administered to 1729 OPC survivors. Survey items included a multisymptom inventory and a validated decisional regret inventory. Associations between regret and symptom scores were analyzed to determine and rank symptom drivers of decisional regret. Results: Nine hundred seventy‐two patients responded reporting a low level of decisional regret overall, although 15.5% communicated "moderate to strong" regret. Overall symptom score and treatment group were statistically significant predictors of decisional regret. Relative to other symptoms, difficulty swallowing and feeling sad were the strongest drivers of decisional regret. Conclusion: OPC survivors provide a robust description of their long‐term outcomes with 15.5% expressing "moderate to high" regret that was significantly associated with late symptom burden and multimodality treatment. Difficulty swallowing was the strongest driver of decisional regret.